Effects of Noise Hazards towards Physiology Especially Heart Rate Performance among Worker in Manufacturing Industry and Their Prevention Strategies: A Systematic Review - Mohd Azrin, Mohd Said; Zinnirah, Wellun; Nor Kamaliana, Khamis (Tehran University of Medical Sciences, 2022)
Background:Occupational noise exposure is one of the environmental factors that pose safety and health risks among workers in factories. This systematic review focuses on the activities that cause noise hazards toward work-ers’ heart rate, other physiological conditions, and strategies to prevent noise exposure in the manufacturing in-dustry. Methods:Through a comprehensive literature review, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and the Cochrane method were used. The appraisal of quality was conducted by using the Critical Appraisal Skills Programme (CASP) to fulfil the selected keywords. Results:Occupational noise exposure not only affects the workers’ most common issues, such as heart rate, but also other physiological factors, such as blood pressure. The outcome showed that different level of continuous noise exposure with high intensity decibels affects the heart rate of the workers. Source, path, receiver wasrecom-mended strategies for basic noise prevention in engineering control. Conclusion:Therefore, noise give significant effects towards human workers in related industry. Study related to noise effects towards heart rate performance led to future prevention and innovation